Reabilitação fonoaudiológica da disfagia em Equipe Multiprofissional de Terapia Nutricional - Maria, Samylla Lopes de Santa (2016)
The Multidisciplinary Team of Nutritional Therapy (EMTN) is mandatory in Brazilian hospitals for determination of ANVISA (SVS / MS No. 337). The EMTN is defined as a formal group consisting of at least one of the following professionals: doctor, nutritionist, nurse and pharmacist. The inclusion of this team speech therapy is optional, although specific speech therapy function in rehabilitation of oropharyngeal dysphagia, affecting a significant number of patients receiving care of the EMTN. Furthermore, the speech therapy also participates in the diagnosis of other swallowing disorders, functional evaluation by defining and performing the treatment in order to enable or re-enable compensate and / or adjust the oral functions affected. OBJECTIVE:To describe and analyze the speech therapy in the rehabilitation of dysphagia frames in patients under the care of the EMTN. METHOD: This is a quantitative and descriptive study. The sample was composed for convenience from the flow of patients in the Hospital of the EMTN (within 60 days) diagnosed with neurogenic oropharyngeal dysphagia or mecânica oropharyngeal dysphagia with severe degree and use of alternative route to power. RESULTS: 32 patients were analyzed, with a mean age of 72.9 years (SD = 12.7). The most frequent medical diagnosis was a progressive neurological disease with 46.9%. The speech diagnosis of progressive neurogenic oropharyngeal dysphagia was the most frequent, with 50%. When comparing the speech therapy markers for dysphagia, evaluation, and hospital discharge, there was statistical significance ranging from p = <0.001 to 0.049. There was a reduction in cases of pneumonia, from 54.1% to 3.1%, as well as statistically significant association between the prognosis of speech therapy Release Oral (LVO) with 68.2% of diet for Oral (VO) in high. As for dietary at discharge is noted that the markers present status of improvement, with statistical significance especially for patients with unique diet orally high. In relation to the types of diet, it was observed that patients with neurogenic progressive dysphagia received high with the highest rate for modified diet (63.6%) and there was improvement in severe status markers for appropriate and especially in patients with mild diet solid at hospital discharge. CONCLUSION: the rehabilitation of dysphagia in patients followed by the EMTN was effective: 65.6% of the patients returned to power for VO exclusively for food or pleasure. This result depended on speech therapy, but from the multi and interaction in EMTN, according to which leverage up the performances of each professional specialty involved